Pendampingan Peningkatkan Kemampuan Literasi dan Numerasi Siswa SD Negeri Fatupisa - I Nyoman Wahyu Esa Wijaya; I Nyoman Suardiasa (Universitas Nusa Cendana, 2023)
The development and changes in the global world are so fast, human resources play an important role in dealing with the changes that occur. If human resources are less qualified and do not have global competitiveness, then of course we will be far behind other nations. Quality human resources and good competitiveness are of course a must for everyone. The results of the PISA survey show that the ranking of Indonesian students' numeracy literacy skills is still at the bottom. In line with the findings in the field and the results of interviews with the head of SDN Fatupisa regarding the numeracy literacy skills of students there are still lacking. This activity aims to improve students' ability in terms of numeracy literacy. The method used is lectures using PowerPoint and question and answer discussions. It was concluded that the response and enthusiasm of the students and teachers at SDN Fatupisa was very good. The results of discussions and questions and answers conducted by resource persons and school members found that most students did not fully understand literacy and numeracy. Then the teachers also become more knowledgeable and have solutions to solving problems at SDN Fatupisa about numeracy literacy.